The concept of the corporation. Issue 7 (3rd October 2019) - Kay, John
Abstract : ABSTRACT This article describes the origins, development, and effect of the markets and hierarchies approach to the theory of the firm. It argues that the approach gives no coherent account of the legitimacy of corporate activity. Additionally, the model bears little relation to the reality of successful corporations. The author describes an alternative tradition for understanding business, owing more to organisation theory, corporate strategy, and business history. In this view, corporations are social organisations. Their competitive advantage is based on distinctive capabilities, the product of their history, their internal architecture and organisational design, and the relationships with employers, customers, suppliers, and commentators.